Learning and asssessment : staff conceptions of final projects for an undergraduate multimedia design degree - Souleles, Nicos (My University, 2006)
This is a qualitative study of teachers’ conceptions of learning and assessment in a final year undergraduate degree in multimedia design. In particular, the focus is on the assessment process of final year projects and what these represent in terms of student learning, progression and potential employability. In the context of Art and Design disciplines, objective criteria of assessment are often difficult to define. How and what we assess reflects the value we place on the final artifact. Underlying this study are theories of ‘deep’ learning that underpin design disciplines. The open-ended interviews with a group of teachers were combined to form a pool of statements about assessing and grading the final project. The data was analyzed using a phenomenographic research approach. A limited number of qualitatively different conceptions of assessment, learning and progression were identified. These conceptions vary with respect to what final year student outcomes represent, and expose some congruence on what to assess and what constitutes learning.
Keywords: Learning; Undergraduates; Multimedia (Art)